That Squeezing Feeling: The Interest Burden and Public Debt Stabilization1 . (5th July 2016) - Debrun, Xavier; Kinda, Tidiane
Abstract: The paper explores the extent to which the pressure of debt service on other spending items may magnify governments' concern for debt dynamics, independently of the public debt level itself. Our empirical analysis identifies thresholds of interest bill indicators beyond which governments appear to intensify efforts to curb the debt trajectory. Hence, in the current context of historically high public debts, a country experiencing high and rising borrowing costs and interest payments would be more likely to enact a more aggressive fiscal consolidation than one benefitting from persistently low interest rates – even though both consolidation paths would be consistent with solvency. This could be an important consideration when setting the appropriate pace of normalization of monetary policy.